2011
DOI: 10.1128/aac.01303-10
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Individual Variation in Intracellular Accumulation of Anti-HIV Nucleoside Analog Metabolites

Abstract: Individual variation in response to antiretroviral therapy is well-known, but it is not clear if demographic characteristics such as gender, age, and ethnicity are responsible for the variation. To optimize anti-HIV therapy and guide antiretroviral drug discovery, determinants that cause variable responses to therapy need to be evaluated. We investigated the determinants of intracellular concentrations of nucleoside analogs using peripheral blood mononuclear cells from 40 healthy donors. We observed individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
(55 reference statements)
2
11
2
Order By: Relevance
“…Similar finding was observed in a study on white blood cells extracted from 9 healthy volunteers (5 females, 4 males) using GAPDH as an endogenous control (Paintsil et al, 2011). The study also observed that ABCC2 expression was not correlated with metabolite levels of ethynylstavudine and lamivudine, but was tentatively to be correlated with zidovudine (P > 0.05) (Paintsil et al, 2011).…”
Section: Comparing Levels Of Abcc2 Expression Between Males and Femalessupporting
confidence: 83%
See 3 more Smart Citations
“…Similar finding was observed in a study on white blood cells extracted from 9 healthy volunteers (5 females, 4 males) using GAPDH as an endogenous control (Paintsil et al, 2011). The study also observed that ABCC2 expression was not correlated with metabolite levels of ethynylstavudine and lamivudine, but was tentatively to be correlated with zidovudine (P > 0.05) (Paintsil et al, 2011).…”
Section: Comparing Levels Of Abcc2 Expression Between Males and Femalessupporting
confidence: 83%
“…The study also observed that ABCC2 expression was not correlated with metabolite levels of ethynylstavudine and lamivudine, but was tentatively to be correlated with zidovudine (P > 0.05) (Paintsil et al, 2011). However, this study was conducted on a small number of subjects with limited statistical power (Paintsil et al, 2011). In contrast, the present study found that gender may potentially influence ABCC2 expression in PBMCs, where males showed greater levels of ABCC2 expression compared to females.…”
Section: Comparing Levels Of Abcc2 Expression Between Males and Femalescontrasting
confidence: 65%
See 2 more Smart Citations
“…It has been recognized for some time that individual parameters, such as gender, age, body weight, and nutrition as well as lifestyle factors, such as alcohol, tobacco, physical exercise, and food preference, contribute to individual variations in drug metabolism [28][29][30][31] . However, it is unknown how these external factors (epi-factors) affect the intrinsic function of drug metabolism.…”
Section: Discussionmentioning
confidence: 99%